2018
DOI: 10.1166/mat.2018.1544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emission Characteristics on Elemental Composition of Selected PVC Ceiling Materials

Abstract: This research work determined the emission characteristics and elemental composition of selected PVC ceiling materials common in Nigerian markets especially during service. This research work determined the emission characteristics and elemental composition of selected PVC ceiling materials common in Nigerian markets. The emission data and elemental structure gave insight to appraise their suitability as ceiling materials. Three PVC ceiling materials were used for this analysis: Nigerian made PVC, layered Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The lower antibacterial activity observed in the PVC-BTHC sections may be related to the non-adhesive nature of the plasticizer which may cause moderate bacterial growth under control conditions [ 9 , 57 ]. A number of studies have discussed the importance of the PM topography in respect to bacterial adhesion, and they have shown that textured surfaces may be beneficial for adhesion, although this cannot be generalized to all materials [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lower antibacterial activity observed in the PVC-BTHC sections may be related to the non-adhesive nature of the plasticizer which may cause moderate bacterial growth under control conditions [ 9 , 57 ]. A number of studies have discussed the importance of the PM topography in respect to bacterial adhesion, and they have shown that textured surfaces may be beneficial for adhesion, although this cannot be generalized to all materials [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the available research institutes are not well equipped with research facilities and there are no financial aids for the agricultural engineers who have flair for agriculture. [20] [21]…”
Section: Limitations To the Design Of Cassava Harvestermentioning
confidence: 99%
“…They observed that in the ferrochrome slag mould, rapid heat loss occurs than silica sand mould. The fast heat loss indicates a high cooling rate and affects casting microstructure [96][97][98][99][100]. The ferrochrome slag casting (grey iron casting) has a small and more fine-sized graphite flake than silica sand mould casting.…”
Section: Ferrochrome Slagmentioning
confidence: 99%